LEARNING MANAGEMENT BASED ON INQUIRY METHOD AND SIMULATIONS TO IMPROVE CRITICAL THINKING SKILLS AND PROBLEM-SOLVING SKILLS OF MATHAYOMSUKSA 1 STUDENTS - Hansena, Supakit; Jumrusprasert, Pattanapong (Journal of Graduate School Sakon Nakhon Rajabhat University, 2024)
The purposes of this research were to 1) compare the learning achievement in science of Mathayomsuksa 1 students before and after learning through the learning management based on inquiry method and simulations, 2) compare students’ critical thinking skills before and after the intervention, and 3) compare students’ problem-solving skills before and after the intervention. The sample group, obtained through purposive sampling, comprised a class of 15 Mathayomsuksa 1 students at Ban Kham Thale So School, Kham Thale So District, Nakhonratchasima Province, in the second semester of the 2022 academic year. The research tools were lesson plans based on inquiry methods and simulations. The instrument for data collection included a learning achievement test, and an assessment test measuring critical thinking skills and problem-solving skills. The results showed that the learning achievement after the intervention reached a mean of 26.00 and a standard deviation of 1.73, accounting for 65 percent, indicating the post-learning achievement score was significantly higher than that before the intervention at the .05 level of significance. The critical thinking skills achieved a mean of 14.73 and a standard deviation of 1.09, or 73.67 percent. The mean of problem-solving skills was equal to 13.53 and the standard deviation of 1.06, accounting for 67.67 percent. Critical thinking and problem-solving skills after the intervention were higher than those before the intervention at the .05 level of significance.